ANALYSIS IMPLEMENTATION GOVERNANCE PRINCIPLES OF BADAN USAHA MILIK DESA (BUMDES) IN BUMDES CIAPUS CIPTA MANDIRI (CCM) IN REGENCY BOGOR - Risdiana Alfaini; Tri Hesti Utaminingtyas; Ayatulloh Michael Musyaffi (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
Badan Usaha Milik Desa (BUMDes) is one of the strategic instruments in efforts to empower the village level economy. Several regulations issued by the government regarding the establishment and management of BUMDes are quite complete. There are differences in the implementation of governance in the field so that the existing rules are still considered not optimal and are still an obstacle to the operationalization of BUMDes. This study aims to analyze the extent to which transparency, responsiveness, professionalism, rule of law, and vision strategy have been implemented and then find out what obstacles Village-Owned Enterprises (BUMDes) face in implementing them. This study used an exploratory qualitative approach with interview methods conducted at Bumdes Ciapus Cipta Mandiri (CCM) in Bogor Regency. The analysis techniques used are data collection, data display and conclusion drawing. The results of this study concluded that CCM BUMDes in Bogor Regency had implemented governance with the principles of transparency, responsiveness, professionalism, rule of law, and vision strategy. This study recommends that future research should involve more BUMDes as samples and apply observational techniques to provide richer insights and a more comprehensive understanding of the phenomenon being investigated.